Floral Ornament as a Key to Understanding the National-Romantic Version of Catalan Modernism - N. A. Kuzina (Ибероамериканские тетради)
The article examines the symbolism of vegetal forms used in Catalan modernism at the turn of the 20th century. Catalan modernism was one of the artistic movements that widely used nature as a source of inspiration. Vegetal elements of decoration were not just aesthetic ornaments, they were filled with historical and cultural symbolism acquiring ideological value. Guided by the national ideals that were formed during the 19th century in the wake of the Renaixença, the artists of Catalan modernism created a symbolic universe. Vegetal ornamentation synthesised and visually conveyed the diversity of ideas of Catalanism, i.e., nationalism, tradition, heroic past and religious sentiment. It resulted in an iconographic program adapted to the distinctive features of Catalan society and, in particular, to the ideological background with which conservative Catalanists identified themselves.